Dental modified method for estimating age in adult individuals - Vilcapoma Guerra, Henry Jesús (2012)
The aim of this study was to develop a specific dental age estimation formula for adults in Lima based on Lamendin´s, Prince – Ubelaker´s and Ubelaker – Parra´s methods. The sample consisted in 50 healthy permanent one-root teeth of adult patients between 25 to 75 years old treated in health centers in Lima city. The applicability of the three dental methods (Lamendin, Prince - Ubelaker and Ubelaker-Parra) were validated to estimate the age of the sample. This was done using the Wilcoxon test that showed that the ages estimated by both, Prince – Ubelaker`s and Ubelaker – Parra`s methods did not have significant difference from the real age, compared with the results of Lamendin that actually showed significant differences. Age estimation was better with Prince – Ubelaker`s method (r = 0.935) compared with Ubelaker – Parra`s method (r = 0.918), so the first method was the most accurate to estimate the age of the sample. Applying the multiple regression test a new formula could be obtained, which is more accurate for age estimation in this adult population of Lima city. The conclusion was that Prince – Ublekar`s and Ubelaker – Parra`s methods are valid for adult age estimation of Lima city, also a more specific dental method for age estimation in a sample of adult population of Lima City was develop.